Economics of milk production and its disposal pattern in Central Gujarat - Mishra, Snehal (Indian Journal of Dairy Science, 2018)
The study has made an attempt to estimate the economics of milk production and its pattern of disposal for different types of milch animals and farm sizes according to land and milch animals. Anand and Dahod were selected purposively from the Central Gujarat. The study has covered a sample of 150 milk producers for in-depth investigation. It was found that average total maintenance cost for land owning category for buffalo, CB cow and indigenous cow per day was Rs. 175.08, Rs. 173.29 and Rs. 115.58 respectively. No significant difference in yield was observed between Anand and Dahod districts across different categories of milk producers. The overall input output ratio on the basis of cost C2 for land owning category was the highest in case of CB cow ( 1.34) followed by buffalo ( 1.20) and same was true for landless milk producers. Overall, dry fodder and concentrate exerted significant influence on value of gross return from buffalo milk production. The production function analysis also indicated that decreasing return to scale prevails in the study area in case of buffalo milk production. Marketable surplus was 89.4 percent and 54 per cent respectively in case of land owning and landless categories of the respondents. The whole quantity of marketable surplus was sold to cooperatives only by the sample farmers. Net profit per year in rearing the buffalo was about Rs. 11000 while it was significantly higher, between Rs. 13517.62 to Rs. 19817.90, in case of CB cow. Assured market and remunerative prices provided by dairy cooperatives can go a long way in enhancing the income of milk producers in the study area if the dry fodder problem, particularly in Dahod, during summer months, and availability of cheap, adequate and hassle free credit is made available to the milk producers for purchasing quality milch animals.